2018
DOI: 10.15252/embj.201899777
|View full text |Cite
|
Sign up to set email alerts
|

Queuosine‐modified tRNAs confer nutritional control of protein translation

Abstract: Global protein translation as well as translation at the codon level can be regulated by tRNA modifications. In eukaryotes, levels of tRNA queuosinylation reflect the bioavailability of the precursor queuine, which is salvaged from the diet and gut microbiota. We show here that nutritionally determined Q‐tRNA levels promote Dnmt2‐mediated methylation of tRNA Asp and control translational speed of Q‐decoded codons as well as at near‐cognate codons. Deregulation of translation upon queuine depletion results in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
165
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 68 publications
11
165
3
Order By: Relevance
“…At this early timepoint of 2 h after inhibitor treatment, we observed changes in DI splicing for only three genes: OGT , as expected; OGA , which encodes the glycosidase that together with OGT controls cellular O-GlcNAc levels; and QTRTD1 , which encodes a subunit of tRNA-guanine transglycosylase, an enzyme that incorporates the hypermodified guanine analog queuosine into the wobble position of some tRNAs (Figure 2A). Although we did not follow-up on the latter observation, we point out that the queuosine tRNA modification is proposed to serve as a nutrient-controlled mechanism to fine-tune protein translation (59). Normalized RNA-sequencing read depths in the regions containing the DIs clearly exhibited increased read depth compared to other introns within the genes (Figure 2B).…”
Section: Resultsmentioning
confidence: 90%
“…At this early timepoint of 2 h after inhibitor treatment, we observed changes in DI splicing for only three genes: OGT , as expected; OGA , which encodes the glycosidase that together with OGT controls cellular O-GlcNAc levels; and QTRTD1 , which encodes a subunit of tRNA-guanine transglycosylase, an enzyme that incorporates the hypermodified guanine analog queuosine into the wobble position of some tRNAs (Figure 2A). Although we did not follow-up on the latter observation, we point out that the queuosine tRNA modification is proposed to serve as a nutrient-controlled mechanism to fine-tune protein translation (59). Normalized RNA-sequencing read depths in the regions containing the DIs clearly exhibited increased read depth compared to other introns within the genes (Figure 2B).…”
Section: Resultsmentioning
confidence: 90%
“…Indeed, recent research showed that RNA modification patterns can change, especially during the response to particular stresses resulting, for instance, in the reprogramming of protein translation . In addition, nutrient deprivation or serum starvation induced U to Ψ conversion, heat shock‐induced m 6 A (or m 6 Am) placement in 5′ UTRs of mammalian mRNAs thereby promoting cap‐independent translation and microbial‐derived micronutrients linked RNA modifications to coordinated decoding of transcriptomes . Furthermore, the identification of RNA editing and RNA modification events in post‐mitotic and adult tissues underscores the notion that RNA modification systems are not necessarily required for development and differentiation, but are dynamically placed, or can be further modified (i.e., Ψ by N1 methylation, m 5 C to various oxidation products, 3‐methylcytosine–3‐methyluridine).…”
Section: Rna Modifications: Potential For Dynamic Regulation Of Rna Pmentioning
confidence: 99%
“…Collectively, the study by Tuorto et al () convincingly shows that the absence of Q affects protein synthesis and that this effect is associated with ER stress caused by a misfolded protein response (Fig ). Nevertheless, several questions remain unsolved.…”
Section: Dietary Queuine and Gut Microbiota‐derived Queuine Regulate mentioning
confidence: 77%
“…Interestingly, Q-starved mice displayed reduced body weight, increased expression of ER stress markers, and reduced mRNA translation, recapitulating the cell-based observations. Collectively, the study by Tuorto et al (2018) convincingly shows that the absence of Q affects protein synthesis and that this effect is associated with ER stress caused by a misfolded protein response (Fig 1). Nevertheless, several questions remain unsolved.…”
mentioning
confidence: 74%